Pathways linking late-life depression to persistent cognitive impairment and dementia - Butters, Meryl A. (Les Laboratoires Servier, 2008)
There is a strong association between late-life depression, cognitive impairment, cerebrovascular disease, and poor cognitive outcomes, including progressive dementia, especially Alzheimer's disease. While neuroimaging evidence suggests that cerebrovascular disease plays a prominent role, it seems that depression alone may also confer substantial risk for developing Alzheimer's disease. The relationships between the prominent cerebrovascular changes, other structural abnormalities, specific forms of cognitive dysfunction, and increased risk for developing Alzheimer's disease among those with late-life depression have been difficult to reconcile. The varied findings suggest that there are likely multiple pathways to poor cognitive outcomes. We present a framework outlining multiple, non-mutually exclusive etiologic links between depression, cognitive impairment, and progressive decline, including dementia. Importantly, the model is both testable and falsifiable. Going forward, using models such as this to inform research should accelerate knowledge acquisition on the depressionldemeniia relationship thai may be useful for dementia prevention, monitoring the impact of depression treatment on clinical status and course of illness.